2016
DOI: 10.1111/nep.12680
|View full text |Cite
|
Sign up to set email alerts
|

Delayed ischaemic preconditioning in the presence of galectin‐9 protects against renal ischaemic injury through a regulatory T‐cell dependent mechanism

Abstract: The renoprotective effect of delayed IPC combined with galectin-9 was superior to IPC alone, through a mechanism related to expansion of regulatory T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Previously we have proved that the renoprotective effect of delayed IPC was partially through a mechanism related to the expansion of Treg cells [8]. Here we found that CD28sa mimicked the renoprotective effects of IPC on kidneys, and in some respects, even better.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Previously we have proved that the renoprotective effect of delayed IPC was partially through a mechanism related to the expansion of Treg cells [8]. Here we found that CD28sa mimicked the renoprotective effects of IPC on kidneys, and in some respects, even better.…”
Section: Resultssupporting
confidence: 58%
“…For the latter, one of the protective mechanisms of IPC involves the upregulation of Treg cells, which negatively regulate the excessive inflammatory reaction in renal ischemic injury [11]. Our previous studies have clarified that IPC also breaks the balance of AKI to some extent [8,12]. Unlike the other immunomodulatory agents, the superagonistic CD28-specific monoclonal antibody (CD28sa MAb, clone: D665) can activate T cells and expand Treg cells selectively without recognition of the first signal by the T-cell receptor [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tim-3 may affect acute kidney injury by regulating Treg cells and further participate in the progression of chronic kidney disease [51]. In renal IRI, Zhan et al [54] found that the protective effect of delayed ischemic preconditioning combined with Gal-9 is better than that of ischemic preconditioning alone, and its effect is mediated by the expansion of Treg cells. Mesenchymal stem cells attenuate sepsis-associated acute kidney injury by the induction of Tregs and inhibition of Th17 cells via the Gal-9/Tim-3 pathway [55].…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-9 is a ␤-galactoside binding protein, which is a urate transporter in the kidneys, is also expressed in myeloid cells, and is known for its role in dendritic cell maturation and inducing apoptosis of promoting iTreg differentiation (151). Combination of galectin-9 pretreatment with ischemic preconditioning offered better protection from IRI than ischemic preconditioning alone (271). The protection correlated with a decrease in IFN␥-producing CD4 ϩ T cells and an increase in the proportion of Foxp3 ϩ Tregs in peripheral blood, spleen, and kidneys.…”
Section: F685mentioning
confidence: 99%